RG7774 (Vicasinabin), an orally bioavailable cannabinoid receptor 2 (CB2R) agonist, decreases retinal vascular permeability, leukocyte adhesion, and ocular inflammation in animal models - Grether, Uwe; Foxton, Richard H.; Gruener, Sabine; Korn, Claudia; Kimbara, Atsushi; Osterwald, Anja; Zirwes, Elisabeth; Uhles, Sabine; Thoele, Janina; Colé, Nadine; Rogers-Evans, Mark; Röver, Stephan; et al. (Frontiers in Pharmacology, 2024)
Introduction Preclinical studies suggest that cannabinoid receptor type 2 (CB2R) activation has a therapeutic effect in animal models on chronic inflammation and vascular permeability, which are key pathological features of diabetic retinopathy (DR). A novel CB2R agonist, triazolopyrimidine RG7774, was generated through lead optimization of a high-throughput screening hit. The aim of this study was to characterize the pharmacology, absorption, distribution, metabolism, elimination, and toxicity (ADMET) profile of RG7774, and to explore its potential for managing the key pathological features associated with retinal disease in rodents. Methods The in vitro pharmacology of RG7774 was investigated for CB2R binding and receptor activation using recombinant human and mouse CB2R expression in Chinese hamster ovary cells, and endogenous CB2R expression in human Jurkat cells, and rat and mouse spleen cells. The ADMET profile was evaluated and the effects of RG7774 on retinal permeability, leukocyte adhesion, and choroidal neovascularization (CNV) were investigated in rodent models of retinal disease. Pharmacokinetic (PK) parameters and the exposure-response relationship were characterized in healthy animals and in animals with laser-induced CNV. Results RG7774 was found to be a potent (EC50: 2.8 nM and Ki: 51.3 nM), selective, and full CB2R agonist with no signs of cannabinoid receptor type 1 (CB1R) binding or activation. The ligand showed a favorable ADMET profile and exhibited systemic and ocular exposure after oral delivery. Functional potency in vitro translated from recombinant to endogenous expression systems. In vivo, orally administered RG7774 reduced retinal permeability and leukocyte adhesion in rodents with lipopolysaccharide (LPS)-induced uveitis and streptozotocin (STZ)-induced DR, and reduced lesion areas in rats with laser-induced CNV with an ED50 of 0.32 mg/kg. Anatomically, RG7774 reduced the migration of retinal microglia to retinal lesions. Discussion RG7774 is a novel, highly selective, and orally bioavailable CB2R agonist, with an acceptable systemic and ocular PK profile, and beneficial effects on retinal vascular permeability, leukocyte adhesion, and ocular inflammation in rodent animal models. Results support the development of RG7774 as a potential treatment for retinal diseases with similar pathophysiologies as addressed by the animal models.